Immunogenicity and safety of a quadrivalent meningococcal tetanus toxoid-conjugate vaccine (MenACYW-TT) in healthy toddlers: a Phase II randomized study. Issue 6 (2nd June 2020) - Vesikari, Timo; Borrow, Ray; Forsten, Aino; Findlow, Helen; Dhingra, Mandeep S.; Jordanov, Emilia
ABSTRACT: Neisseria meningitidis: can lead to invasive meningococcal disease to which young children are particularly vulnerable. We assessed the immunogenicity and safety of Sanofi Pasteur's investigational quadrivalent (serogroups A, C, Y, and W) meningococcal tetanus-toxoid conjugate vaccine, MenACYW-TT, as a single dose, in healthy meningococcal vaccine-naïve toddlers versus a licensed conjugate vaccine MCV4-TT (NCT03205358). In this Phase II study conducted in Finland, 188 toddlers aged 12–24 months were randomized 1:1 to MenACYW-TT or MCV4-TT. Serum bactericidal antibody assays using human complement (hSBA) and baby rabbit complement (rSBA) measured antibodies against each serogroup before and 30 days after vaccination. Participants were monitored for immediate adverse events (AEs) and post-vaccination AEs for 30 days. All analyses were descriptive. All 188 participants completed the study. The Day 30 hSBA seroresponses (hSBA titer <8 at baseline and post-vaccination titer ≥8, or ≥8 at baseline and ≥4-fold increase post-vaccination) were comparable between participants receiving MenACYW-TT (96.7–100%), and MCV4-TT (86.0–100.0%) for each serogroup. Most unsolicited AEs were of Grade 1 or Grade 2 intensity. There were no immediate hypersensitivity reactions, and no AEs or serious AEs leading to discontinuation from the study. In this exploratory study, MenACYW-TT vaccine was well tolerated and immunogenic. If confirmed in Phase III, a single dose of the MenACYW-TT vaccine may show promise as an alternative vaccine option for toddlers receiving meningococcal vaccination for the first time.